Pengujian Pengaruh CAR dan Pembiayaan Murabahah Terhadap Profitabilitas dengan DPK sebagai variabel Moderasi - Lestari, Mifta Dwi Wiji; Alfinur, Alfinur; Setyowati, Supami Wahyu (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam 45, 2021)
Abstract This research was conducted to determine whether the effect of the independent variables: CAR and Murabahah Financing on the dependent variable of profitability with the moderating variable of TPF in Islamic Commercial Banks (BUS) in Indonesia from 2015-2019. The method used in this research is a quantitative approach. The population used in this research is BUS that is registered in the Financial Services Authority in 2020 totaling 14 companies. The sample used was 6 BUS that fit the test criteria. The data studied were time series data in tools, namely Smart Partial Least Square (SmartPLS) 3.3.2. The results of the research conducted are CAR has a positive and significant impact on profitability, Murabahah financing has a the form of annual reports. The data analysis technique used is PLS with data analysis positive and significant impact on profitability, TPF moderates the effect of CAR on profitability, TPF moderates the effect of Murabahah Financing on profitability. Keywords: CAR; Murabahah Financing; profitability; DPK